Iván Oñate: Anatomy of a Poet in the Land of Shadows - Salgado Jácome, Pablo (2026)
Iván Oñate is, without a doubt, one of the most important voices in Ecuadorian and Ibero-American poetry. Through a lived and long-shared relationship, the author offers a journey through the life and work of the poet—his thought and his way of conceiving the literary craft. This work provides an approach to his poetry and narrative, to his ideas, to the authors who shaped his writing, and to his cultural references such as cinema and music. It also includes a brief analysis of each of the books he published in Ecuador and abroad, works that garnered not only devoted readers but also critical acclaim. His sudden passing in September 2025 leaves behind a literary legacy that is valuable, profound, and vital.